Towards Mobile UX Evaluation and Improvement in Startups: A Case Study on the Adoption of User Experience Questionnaire and Hierarchical Task Analysis - Sousa, Francisco William; Araújo, Allysson Allex; Gomes, Francisco A. Almada; Moreira Neto, Maurício (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Beyond focusing on entire markets rather than developing tailor-made software for specific customers, startups with business models based on digital products for mobile applications leverage the relevance of mobile User eXperience (UX) to reflect the software quality and success of scalable businesses. However, due to the dynamic and uncertain market nature, it is usually challenging for startups to balance a fast-paced product delivery with a systematic UX evaluation and improvement process. Even with the recognized relevance of academia and the software industry, there is still a lack of empirical research addressing mobile UX in startups. Given this opportunity, our research aims to investigate the perception of the team of a startup in a scale-up stage on the adoption of the User Experience Questionnaire and the Hierarchical Task Analysis for evaluating and improving mobile UX. To this end, we approached a qualitative methodological path in the form of a single and instrumental case study. As for the results, we obtained a multi-method and empirical diagnosis of the team’s perception from four analytical perspectives: i) comparison with the previous process, ii) difficulties, iii) lessons learned, and iv) expectations. As a major contribution, we highlight the opportunity to advance in understanding the particularities of evaluation and improvement of mobile UX in the context of startups that work remotely, including the sharing of reflections that may be useful for other companies and researchers.